Phenol remediation by Ipomoea aquatica forssk and toxicity evaluations on post-treatment plant extracts - Lee, Siew Yi (2019)
Widespread use of phenol in the manufacturing industries and oil refineries resulted in unprecedented phenol leakage into the environment affecting drinking water standards and human health conditions. Phytoremediation was proposed as an environment friendly and cost-effective phenol remediation approach. In this context, Ipomoea aquatica Forssk, a native plant commonly found in contaminated sites and has ability to remediate heavy metals, was chosen as the candidate for study. This research aimed to elucidate the oxidative effects, efficiency and mechanisms of phenol remediation by I. aquatica Forssk as well as to evaluate the toxicities of the post-remediated plant extracts using in vitro and in vivo animal model systems. I. aquatica Forssk seedlings were subjected to water spiked with 50, 100, 200 and 300 mg/L phenol, respectively. Low phenol concentration produced significantly taller plants (50 mg/L phenol: 101.9 ± 4.4 mm) compared to Control plants (85.2 ± 11.8 mm). At 300 mg/L phenol, plants were stunted, had scars on stems and yellowish leaves with reduced palisade layer and photosynthetic pigments. The tolerance threshold for I. aquatica Forssk was recorded as 300 mg/L whereby 50% of the treated plants were dead, while the remaining suffered severe oxidative stress with disrupted membrane integrity (severe electrolyte leakage of 68.0 ± 7.9%). I. aquatica Forssk remediated phenol optimally at 100 mg/L with a rate of 2.3 ± 0.0 mg L⁻¹ day⁻¹, which was equivalent to removing 273.8 ± 15.3 mg phenol within 14 days. The phenol was degraded through the catechol cleavage pathway with a root peroxidase activity of 118.4 ± 13.0 U/µg protein and catechol production of 2.7 ± 0.0 mg/L. Comparative proteomic analysis showed that I. aquatica Forssk exhibited compensatory growth upon exposure to 100 mg/L phenol by mitigating oxidative stress using more antioxidants and metabolising phenol as alternative carbon source in glucose assimilations. Evaluation of the toxicities of the plant extract (using 140 - 500 mg/L) on Zebrafish embryos revealed no fatal toxicities at 320 mg/L as the larvae experienced minor scoliosis and pericardium oedema while LC₅₀ BALB/c mice with oral administration of 2 000 mg/kg (acute) and 50 - 100 mg/kg/day (sub-acute) plant extracts did not record any mortality or severe toxicity symptoms. The LD₅₀ of orally administered extracts was regarded as > 2 000 mg/kg. In accordance to the Globally Harmonised Classification System for Chemical Substances and Mixtures, the data obtained categorised post- remediation I. aquatica Forssk plants into Category 5: nontoxic substance. Overall, the data obtained highlights the potential of I. aquatica Forssk as a phenol phytoremediator and the treated plants could be used as animal feeds.